Rethinking Indebtedness according to the Principles of Justice and Equality (Universitas Negeri Semarang, 2022)
The law's objective is to uphold the principle of justice. Contractual debts, interest-bearing debts, unsecured debts, and debts with payment terms are all included in restructuring plans. All debts must be accompanied by a contract. If the business defaults, the contract serves as proof of debt. This research focuses on Indonesia's bankruptcy law. This study employs an empirical qualitative legal method. The study recommends categorizing debt according to its source, duration, function, and collateral. Debts classified as restructuring must waive their collateral rights. This debt grouping is consistent with finance's capital structure theory. This research will revolutionize the current concept of debt restructuring. The study will serve as a resource for all business actors who have documented debt. Debt is uncommon in developing countries such as Indonesia. Entrepreneurs in developing countries have established business relationships based on mutual trust. The study's limitation is that it does not take industry type into account. Additionally, this research has implications for a firm's total cost of capital as a result of changes in the risk model and creditor roles, particularly in developing countries. This study proposes a system of debt classification based on principles of justice and equity. This classification is made not only on the basis of the guarantee's type, but also on the basis of the agreement's duration and financial principles. The purpose of this study is to examine bankruptcy law in developing countries. Knowledge of bankruptcy law will add value to investors and banks on a global scale.